The Implementation of Tartil Method in Improving Elementary School Students’ Ability in Reading Alquran - Syafril, Syafrimen; Yaumas, Nova Erlina (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2017)
This study is aimed at describing the implementation of Tartil method as an alternative to eliminate Alquran illiteracy among elementary school students. The study was conducted through two phases of explanatory mixed methods designs. Quantitative method was applied in the first phase (true experiment; pretest-post test one group design) involving 78 pupils of two schools who were Qur’an illiterate. Qualitative method was applied in the last phase (multi case-multi site case study design) involving 13 pupils and 2 teachers who implemented the method in their classroom. Data of the first phase was collected through oral test analyzed through descriptive statistics of SPSS (Statistical Package for Social Science) Windows 18.0. Further, the second phase data was collected through in depth interview thematically analyzed by Nvivo 8. The findings of the study indicate the improvement of students’ ability in reading Qur’an after Tartil method was implemented (57.57% Good & 42.43 % Moderate). Data of the second phase implies that the success of the method is pursuant to four prominent factors, namely; (i) the method is truly enjoyable, understandable, simple and practical, (ii) the materials are systematically and precisely presented, (iii) the materials are easy to remember as they are colorful, (iv) it is possible to teach the students how to read Qur’an in murotal way through this method.